Physiological Response of Crocidolomia pavonana to the Calophyllum soulattri Active Fraction - EDY SYAHPUTRA; DJOKO PRIJONO; DADANG DADANG; SYAFRIDA MANUWOTO; LATIFAH KOSIM DARUSMAN (HAYATI Journal of Biosciences, 2006)
The objective of this study was to evaluate the physiological response of the cabbage head caterpillar Crocidolomia pavonana treated with an active fraction of Calophyllum soulattri bark extract. Extraction of the test plant materials were performed with maceration method using methanol, continued by counter-current distribution separation in ethylacetate and water. Methanol fractionation of C. soulattri was performed by vaccuum liquid chromatography and the bioassays were conducted by a leaf-feeding method. The results showed that the dichloromethane fraction of C. soulattri had strong insecticidal activity against C. pavonana larvae, with LC50 of 0.05%. Sublethal treatments with the active fraction at LC15, LC50, and LC85 reduced the relative growth rate of the fourth instars by 48.9-94.1%. The treatments with the fraction at LC15 and LC50 to the fourth instars reduced the activity of invertase and protease enzyme by 20.7-24.1 and 14.4-25.14%, respectively, but increased the activity of trehalase by 26.7-120% as compared with controls. Key words: Physiological response, Crocidolomia pavonana, Calophyllum soulattri, botanical insecticide